A real-world cost-effectiveness study of vancomycin versus linezolid for the treatment of late-onset neonatal sepsis in the NICU in China - Linjun Xie; Leyun Ding; Lian Tang; Zuming Yang; Dan Wu; Wenjuan Wang; Juehui Mao; Lu Shi; Chun Liu; Lufen Duan; Jinhui Xu; Qin Zhou; et al. (BMC, 2023)
Abstract Background and objective Currently, the detection rates of methicillin-resistant S. aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (MRCoNS) in the blood cultures of neonates with sepsis exceed the national average drug resistance level, and vancomycin and linezolid are the primary antibacterial drugs used for these resistant bacteria according to the results of etiological examinations. However, a comprehensive evaluation of their costs and benefits in late-onset neonatal sepsis in a neonatal intensive care unit (NICU) has not been conducted. This study aimed to compare the cost and effectiveness of vancomycin and linezolid in treating neonatal sepsis in the NICU. Methods A cost-effectiveness analysis of real-world data was carried out by retrospective study in our hospital, and the cost and effectiveness of vancomycin and linezolid were compared by establishing a decision tree model. The drug doses in the model were 0.6 g for linezolid and 0.5 g for vancomycin. The cost break down included cost of medical ward, NICU stay, intravenous infusion of vancomycin or linezolid, all monitoring tests, culture tests and drugs. The unit costs were sourced from hospital information systems. The effectiveness rates were obtained by cumulative probability analysis. One-way sensitivity analysis was used to analyze uncertain influencing factors. Results The effectiveness rates of vancomycin and linezolid in treating neonatal sepsis in the NICU were 89.74% and 90.14%, respectively, with no significant difference. The average cost in the vancomycin group was ¥12261.43, and the average cost in the linezolid group was ¥17227.96. The incremental cost effectiveness was ¥12416.33 cost per additional neonate with treatment success in the linezolid group compared to vancomycin group at discharge. Factors that had the greatest influence on the sensitivity of the incremental cost-effectiveness ratio were the price of linezolid and the effectiveness rates. Conclusions The cost for treatment success of one neonate in linezolid group was ¥5449.17 more than that in vancomycin group, indicating that vancomycin was more cost-effective. Therefore, these results can provide a reference for a cost effectiveness treatment scheme for neonatal sepsis in the NICU.